Noncovalently connected supramolecular metathesis graft copolymers: One-pot synthesis and self-assembly. (March 2019) - Ding, Liang; Li, Juan; Jiang, Ruiyu; Wang, Lingfang; Song, Wei; Zhu, Lei
Graphical abstract: Three types of noncovalently connected amphiphilic supramolecular graft copolymers were prepared relying on ring-opening metathesis polymerization and host–guest interaction via a two-feed procedure in one-pot; The polymers further self-assemble into supramolecular nanostructures with diverse morphologies. Highlights: The noncovalently connected amphiphilic graft copolymer was synthesized in one-pot. Supramolecular block and alternating amphiphilic graft copolymers were constructed. The graft-based amphiphilic copolymers self-assemble to the irregular nanostructures. Abstract: For the first time, noncovalently connected supramolecular polymers were prepared by ring-opening metathesis polymerization (ROMP) and host–guest interactions in a one-pot process. An adamantane-based oxanorbornene dicarboximide derivative was first prepared, and then ROMP was accomplished in a single operation, followed by efficient complexation between cyclodextrin and adamantane moieties to form amphiphilic supramolecular graft copolymers via a two-feed procedure in one-pot. Subsequently, amphiphilic supramolecular block and alternating graft copolymers were constructed using a similar technique via the copolymerization with cyclooctene in one-pot. Importantly, the degree of polymerization and molecular weight distribution of these supramolecular polymers were well controlled, and further they self-assembled into supramolecular nanostructures with diverse morphologies in aqueous solution. It is expected that this research will provide a new direction for designing and constructing noncovalently connected supramolecular metathesis polymers.